The investigation of Relationship Between Leadership Practices, Role Stressor, Religious Coping and Job Insecurity With Job Stress Among University Academician In Pahang And Jogyakarta - Triantoro, Safaria (2011)
Stress can be found in all aspects of life. Stress is inseparable in every individual life aspect. Stress may have positive effects, but many cause negative effects. One type of stress that can engender negative effects is job stress. Job stress is major threats to modern organization that causes many negative impacts, either for employee or organization. In education organization, especially at higher-education setting, many studies concluded that lecturer, staff or administration personnel reported from middle level to higher level of job stress (Donders et al., 2003; Boscolo et al., 2008; Leung et al., 2000; De Nobile, and McCormick, 2007). This study aims to investigate the relationships between role ambiguity, role conflict, leadership practices to job stress and test the role of religious coping as moderator variable and job insecurity as a mediator variable to job stress in Malaysian academic staff in Pahang, Malaysia and Javanese academic staff in Indonesia's context. Beside, the present study wants to test moderation-mediation model of job stress in cross-cultural study. ANOVA and Path analysis using structural equation model used to test the research hypothesis. This study used mixed method cross cultural approach to test and examined theory and model of moderated-mediated job insecurity-stress among academic staff in two countries. In general it can be concluded that some independent variables have a significant relationship with job stress, but some others have no effect. The result of the mediation model showed that job insecurity significantly mediate the relationship between antecedents with job stress only in Pahang academic staff, not for Jogjakarta academic staff. While, religious coping as a moderator variable shows a variance result in two countries. In Pahang academic staff, religious coping significantly buffer the effect of antecedents to job insecurity, but not significantly buffer relationship between antecedents to job stress. In Jogjakarta academic staff, religious coping just significantly buffer the effect of the antecedents-job stress model, but not significantly moderate the effect of the antecedents-job insecurity model. It could be concluded that the moderated-mediated model in this study showed variant between two countries. Cultural and contextual factors may have influenced the variant result of this study, and this finding need to explore further.